Parents’ perception or children’s perception? Parental involvement and student engagement in Chinese middle schools - Keqiao Liu; Yong Zhao; Miao Li; Wenjing Li; Yang Yang (Frontiers in Psychology, 2022)
It is widely held that parental involvement plays a key role in enhancing student engagement, but less is known about whether and how parents’ and their children’s perceptions of different types of parental involvement relate to dimensions of student engagement, especially in the Chinese context. By surveying 2,219 students and their parents from nine middle schools in eastern China, this study found that only children’s perceptions of certain types of parental involvement (e.g., parent–child communication), rather than those of their parents, correlated with student engagement (i.e., behavioral engagement, emotional engagement, and cognitive engagement). Further, different types of parental involvement presented varied relationships with dimensions of student engagement. This study deepens our understanding of the dynamic interplay between parental involvement and student engagement in view of parents’ and children’s perceptions.